N-doped carbon layer coated thermally exfoliated graphene and its capacitive behavior in redox active electrolyte. (April 2015) - Yan, Yinan; Kuila, Tapas; Kim, Nam Hoon; Lee, Seung Hee; Lee, Joong Hee
Abstract: A nitrogen-doped carbon layer coated thermally exfoliated graphene (NC-TEG) is prepared by in-situ polymerization of p-phenylene diamine (PD) with thermally exfoliated graphene (TEG) and subsequent high temperature pyrolysis (600 °C for 1 h in argon gas environment). Fourier transfer infrared spectroscopy, X-ray photoelectron spectroscopy, and scanning electron microscopy confirm the formation of poly-(p-phenylene diamine) layers on the TEG surfaces with a nitrogen doping level of ~6.1%. Physisorption analysis indicates that NC-TEG not only has the enlarged surface area, but also forms hierarchical three dimensional structures with several micro and meso-pores compared to pristine TEG. Due to the synergic effect of nitrogen atoms in the carbon structures and augmented surface area, the capacitance measured from cyclic voltammetry and galvanic charge–discharge increases to 282.5 F g −1 from the 95.1 F g −1 of TEG. Moreover, the PD monomer acts as a reversible faradaic agent. The capacitive performance of the NC-TEG electrode is investigated in different mixed electrolytes. The specific capacitance is significantly increased to 635.6 F g −1 in a mixed electrolyte of 0.025 M PD and 2 M KOH. After 10, 000 cycles, the capacitive retention shows remarkable stability as high as 87.4%.